Integration of Quantity Discount Pricing into Newsvendor Model - Haryadi Sarjono; Jeff Fernandez; Randy Jeremaiah; Randy Tjhie; Bachtiar H Simamora (International Journal of Supply Chain Management, 2020)
This research was done with a purpose to find out the solution of supply shortage problem which often occurs in supplying companies in Indonesia, which resulted by non-optimized order quantity. Quantity Discount Pricing Integrated Newsvendor Model (this term will further be called as Extended Newsvendor) was examined then having its performance compared with subjective method which has already been used by the companies. The comparison was done to discover which method is able to reduce the potential shortage of supplies, total cost of each unit, age of inventory, and order frequency. Extended Newsvendor method was chosen to be examined in the first place due to its assumption which was deemed suitable with the actual condition that is encountered by the companies, where the demand happens stochastically, and quantity discount pricing policy is applied. The calculation that utilizes 5 years of the company historical data, this research find that the Extended Newsvendor method is generally able to improve the performance of the order quantity medium-sized companies but is unable to improve the performance of the order quantity of small-sized companies